(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to investigate the current use of the traditional herbal formula Doc hoat tang ky sinh in the treatment of sciatica at the Department of Traditional Medicine, Chau Thanh district Medical Center, Hau Giang province, and to assess its therapeutic effectiveness and associated adverse reactions. Methods: A descriptive cross-sectional study was conducted on 372 inpatients from January to December 2024. Data were collected using a standardized questionnaire, medical record review, and face-to-face interviews. The study variables included: the prescription rate of Doc hoat tang ky sinh, dosage, duration of use, adverse effects, and treatment adherence. Data analysis was performed using SPSS version 25.0. Results: The prescription rate of Doc hoat tang ky sinh was 57%. The most commonly used dosage was 15-30 g/day (75.5%), with the majority of patients using the formula for 7-14 days (57.5%). Treatment adherence was relatively high, with 62.7% of patients fully complying with the prescribed regimen. Adverse reactions were rare, with only 0.5% of patients experiencing mild gastrointestinal disturbances. Conclusion: Doc hoat tang ky sinh is widely used in district-level clinical practice for treating sciatica, with appropriate dosage and treatment duration, minimal side effects, and relatively high patient adherence. These findings provide a practical basis for further research on the efficacy and safety of this formula in broader clinical settings.